2009
DOI: 10.1111/j.1600-9657.2009.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of severe dentoalveolar trauma on the quality‐of‐life of children and parents

Abstract: -Background/Aim: This investigation assessed the effects of dental trauma on the perception of pain and quality of life (QoL) of patient-parent pairs for a year following severe injuries. Sample: A visual analogue scale (VAS) was used to assess the pain of injury and treatment for 27 individuals 8-20 years and their parents. The Child Oral Health Quality of Life (COHQoL) survey was used to assess the effects of dental injuries on the QoL of 23 children aged 8-14 and their parents. Results: Mean VAS scores reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 27 publications
5
108
1
3
Order By: Relevance
“…The child's oral health-related quality of life (OHRQoL) was measured using a short form of the Child Perceptions Questionnaire (CPQ [11][12][13][14]. 27 The Impact Short Form (ISF-16) CPQ [11][12][13][14] was developed through item impact methodology and is composed of 16 items comprising four oral health domains (oral symptoms, functional limitations, emotional well-being and social well-being). The participant is asked 'In the past few weeks how often have you [had/been item] because of your teeth or mouth?'…”
Section: Measures Usedmentioning
confidence: 99%
See 3 more Smart Citations
“…The child's oral health-related quality of life (OHRQoL) was measured using a short form of the Child Perceptions Questionnaire (CPQ [11][12][13][14]. 27 The Impact Short Form (ISF-16) CPQ [11][12][13][14] was developed through item impact methodology and is composed of 16 items comprising four oral health domains (oral symptoms, functional limitations, emotional well-being and social well-being). The participant is asked 'In the past few weeks how often have you [had/been item] because of your teeth or mouth?'…”
Section: Measures Usedmentioning
confidence: 99%
“…27 These findings are also consistent with previous research which has identified a number of different visible dental differences (eg malocclusion, dental trauma, severe fluorosis and hypodontia) that are associated with worse OHRQoL in children. 9,11,12,14,15,29,30 Of the OHRQoL domains, it was the impact on emotional and social well-being that was most noticeable. Again, this is consistent with earlier findings which suggest poor dental aesthetics may have a number of psychosocial impacts on children's OHRQoL.…”
Section: Findings In Relation To Oral Health-related Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Berger et al (6) investigated the impacts of severe dental injuries (i.e. luxation or avulsion injuries) on children attending a dental hospital for treatment and found that 64% of children aged between eight and 10-years reported feeling concerned about what others thought about their mouth, 55% felt upset and 45% felt shy or embarrassed as a result of their dental injury.…”
Section: Introductionmentioning
confidence: 99%